Stakeholders and New Venture Growth in Africa - Zahoor, Nadia; Nwoba, Arinze (Routledge, 2024)
This chapter delves into the dynamic and multifaceted landscape of new venture growth in Africa. Its primary focus is on the role played by stakeholders in shaping the entrepreneurial ecosystem on the continent. This article draws insights from stakeholder theory to elucidate the various stakeholders that influence new venture growth in Africa. It explores how each stakeholder group contributes to or hinders the growth of new ventures. The new ventures in Africa face unique challenges. but the potential offered by stakeholders in terms of collaboration, trust-building, and resource mobilization for new venture growth cannot be ignored. We identify stakeholders as a catalyst for enhancing resource access, promoting ethical and sustainable practices, facilitating access to networks, enhancing financial inclusion, supporting the entrepreneurial ecosystem, and building trust that is conducive to new venture growth. We conclude this article by discussing implications and offering future directions.
Keywords: Stakeholders; stakeholder theory; new ventures; entrepreneurship; Africa